Silver nanoparticle-loaded contact lenses for blue-yellow color vision deficiency - Salih,AE; Shanti,A; Elsherif,M; Alam,F; Lee,S; Polychronopoulou,K; Almaskari,F; AlSafar,H; Yetisen,AK; Butt,H (Physica Status Solidi A: Applications and Materials Science, 2021)
Contact lenses can be functionalized to offer advanced capabilities transcending their primary applications in vision correction and cosmetics. Herein, 40 and 60 nm spherical silver nanoparticles (SNPs) are integrated within poly(2-hydroxyethyl methacrylate) (pHEMA) contact lenses toward fabrication of SNP-loaded contact lenses with excellent optical and material properties as wearables for blue-yellow color vision deficiency (CVD) patients. The morphology and optical properties of the SNPs are characterized prepolymerization using the transmission electron microscopy (TEM) and an optical spectrophotometer. Then, the transmission spectra of the SNP-loaded contact lenses at different concentrations along with the wettability and water content are measured, to demonstrate the effect of NPs’ addition on the lenses’ optical and material characteristics. Results indicate that the transmission spectra of SNP-loaded contact lenses, with optimum concentrations, filter out problematic wavelengths of visible light (485–495 nm), which will facilitate better color distinction for blue-yellow CVD patients. The contact lenses’ optical properties are analogous to the commercial colorblind glasses, indicating their effectiveness as color filtering wearables. Finally, the cytobiocompatability analysis of the contact lenses to RAW 264.7 culture of cells shows that they are biocompatible, and the cell viability remains higher than 75% after 24 h in contact with the lenses.